Silicon-containing thiol-specific bioconjugating reagent - Zhang, Zhenguo (2024)
A new bioconjugation reagent containing silicon has been developed for the selective reaction with thiols. The inclusion of silicon significantly improves chemoselectivity and suppresses retro processes, thereby exceeding the capabilities of traditional reagents. The method is versatile and compatible with a broad range of thiols and unsaturated carbonyl compounds and yields moderate to high results. These reactions can be conducted under biocompatible conditions, thereby making them suitable for protein bioconjugation. The resulting conjugates display good stability in the presence of various biomolecules, which suggests their potential application for the synthesis of antibody-drug conjugates. Furthermore, the presence of a silicon moiety within the conjugated products opens up new avenues for drug release and bridging inorganics with other disciplines. This new class of silicon-containing thiol-specific bioconjugation reagents has significant implications for researchers working in bioanalytical science and medicinal chemistry and leads to innovative opportunities for advancing the field of bioconjugation research and medicinal chemistry.